Burnout among Indian Maternity Care Providers during COVID-19 Pandemic - Paul, Sayanti; Joycerani, D; Upadhyaya, Mansi; Sanyal, Poushali; Pal, Arghya (Journal of Maternal and Child Health, 2022)
Background: Occupational burnout among healthcare providers has been a matter of focus since many years. Burnout can involve emotional and physical exhaustion and cause reduced acknow-led